Criminal Trajectories: A Developmental Perspective - Day, David M. (Psychoanalytic Crossroads, 2019)
An exploration of criminal trajectories, placing them in a developmental contextOver the past several years, notions of developmental trajectories—particularly criminal trajectories—have taken hold as important areas of investigation for researchers interested in the longitudinal study of crime. This accessible volume presents the first full-length overview of criminal trajectories as a concept and methodology and makes the case for a developmental approach to the topic.The volume shows how a developmental perspective is important from a practical standpoint, helping to inform the design of prevention and early intervention programs to forestall the onset of antisocial and criminal activity, particularly when it begins in childhood. Crime in this view does not suit a one-size-fits-all model. There are different types of criminals who develop as the result of different types of developmental factors and experiences. By considering what risk factors may set the stage for later crimes in certain circumstances, the authors argue that we may be able to intervene at any point along the life course and, if addressed early enough, prevent criminal behavior from taking root.Criminal Trajectories offers a comprehensive synthesis of the findings from numerous criminal trajectory studies, presented through a multi-disciplinary lens. It addresses the policy and practice implications of these findings for the criminal justice system—including a critique of current sentencing and incarceration practices—and presents twelve recommendations informed by developmental frameworks for future work